2015
DOI: 10.7554/elife.10499
|View full text |Cite
|
Sign up to set email alerts
|

Successful retrieval of competing spatial environments in humans involves hippocampal pattern separation mechanisms

Abstract: The rodent hippocampus represents different spatial environments distinctly via changes in the pattern of “place cell” firing. It remains unclear, though, how spatial remapping in rodents relates more generally to human memory. Here participants retrieved four virtual reality environments with repeating or novel landmarks and configurations during high-resolution functional magnetic resonance imaging (fMRI). Both neural decoding performance and neural pattern similarity measures revealed environment-specific h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
90
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 56 publications
11
90
1
Order By: Relevance
“…In sum, the sigmoidal response pattern we observe in the hippocampus provides novel evidence for an abrupt, remapping-like response to a linearly changed spatial context in humans, consistent with a recent report showing consequences of such a response in multi-modal pattern completion [45] and with pattern separation and completion during memory disambiguation in virtual reality [44]. Participants were trained to ceiling so as to form distinct and separate memories for the two original environments.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In sum, the sigmoidal response pattern we observe in the hippocampus provides novel evidence for an abrupt, remapping-like response to a linearly changed spatial context in humans, consistent with a recent report showing consequences of such a response in multi-modal pattern completion [45] and with pattern separation and completion during memory disambiguation in virtual reality [44]. Participants were trained to ceiling so as to form distinct and separate memories for the two original environments.…”
Section: Discussionsupporting
confidence: 67%
“…Pattern separation in the hippocampus might accentuate small differences, rather than being attracted to a different fixed point, like the familiar pattern of the baseline environments in the present study and in the work by Wills et al [22]. In addition, although pattern separation has been observed during virtual reality navigation [44], putative attractor dynamics are characterized by the emergence of a nonlinear response profile over time ( Figure 4C). …”
Section: Discussionmentioning
confidence: 69%
“…Importantly, our study extends beyond the existing evidence for hippocampal pattern completion from rodent and human studies that rely on representations of spatial locations (Kyle et al, 2015; Leutgeb et al, 2007; Miller et al, 2013; Neunuebel and Knierim, 2014; Stokes et al., 2015). In particular, such work has been limited in demonstrating the link between hippocampal-based spatial codes and choice behavior.…”
Section: Discussionmentioning
confidence: 51%
“…The object cues during the DMTM task provided partial information for retrieving the correctly paired face or place associate through pattern completion. It is likely that pattern separation was involved both during encoding of the paired associates and potentially influenced what information was available during retrieval (Kyle et al, 2015). However, the specificity of the item reinstatement signatures we observed during retrieval is consistent with a “filling in” of item-specific mnemonic information through pattern completion.…”
Section: Discussionmentioning
confidence: 99%
“…1b. Recent neuroimaging studies using multivariate classification approaches have also demonstrated that neural patterns are largely uncorrelated in the DG/CA3 subregion 56 . Recently, ultrahigh-resolution 7T fMRI was used to demonstrate that the DG, but not other hippocampal subfields or medial temporal cortices, exhibits distinct neural patterns for similar items, thus suggesting that the human DG is perhaps selectively engaged in pattern separation 57 .…”
Section: Hippocampal Pattern Separation and Episodic Memorymentioning
confidence: 99%